Monetary Systems of Ukraine: Past and Present - Reverchuk, Serhij; Skomorovych, Iryna; Sauers, Daniel A. (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
The paper analyzes the development of monetary systems in Ukrainian lands from ancient times to current days, researches the evolution of their structural elements, and traces the main rules set by the central bank for economic entities in the sphere of money emission and use. A comprehensive and operational analysis of the functioning of the monetary system of Ukraine in the conditions of economic and political crisis is made.